Karol Szymanowski and Richard Strauss: Of Diverging Epiphanies - Cadrin, Paul (Canadian University Music Review / Revue de musique des universités canadiennes, 2004)
According to the philosopher Charles Taylor, since the beginning of the nineteenth century, with the advent of Romanticism, the work of art is defined by its epiphanic character. It is a manifestation of something of the highest moral or spiritual significance; this manifestation is not merely subjective, in which case it would be inaccessible to scholarly inquiry, but it has an objective character. The Third Symphony, op. 27, by Karol Szymanowski is analyzed in the light of Taylor's concept. The Deutsche Motette, op. 62, by Richard Strauss, which is based on a text similar to the one used by Szymanowski, serves as a foil to buttress the findings.